P-125 Delirium – a forgotten phenomenon. (20th March 2022) - Ritchie, Amy; Stone, Carol
Abstract : Background: Delirium is a common and distressing neurocognitive syndrome arising from 'acute global brain dysfunction'. It is a highly prevalent complication amongst palliative care patients affecting between 42%-88% of individuals. Significant morbidity and mortality is associated. To this end, early and effective recognition is a critical aspect of a comprehensive management approach. Methods: We conducted a clinical audit with the aim of determining the prevalence of delirium amongst our population cohort and, evaluating the effectiveness of diagnostic screening when compared with nationally accepted standards. A retrospective chart review of inpatient admissions over a 3-month period was undertaken. Data was tabulated on Microsoft Excel and underwent descriptive analysis against the following defined standards; Assessment of cognition in 100% of patients on admission or within 24–hours Delirium screen in 100% of patients with abnormal cognition If screening is deemed inappropriate, it should be documented in 100% of patients Results: In total 55 inpatient admissions were reviewed, with delirium developing in 53% of this population. A formal cognitive assessment was undertaken in 17% of patients however 85% of patients subjectively required assessment for confusion. No patients underwent a formal delirium screen or documentation to this effect. Of those individuals with documented confusion, 87% subsequently developed delirium. In those with subjective confusion but not documented 71% developed delirium. A total of 35% of patients developed delirium in whom subjective confusion was negative. Conclusion/Lessons Learned: Despite the presence of impaired cognition in significant numbers, formal assessment of delirium is not routine practice. It is evident that formal assessment is likely to unveil an underlying cognitive impairment process and facilitate early intervention. We have subsequently delivered multidisciplinary education and implemented a management pathway to reduce the burden of delirium in our inpatient unit. We plan to reaudit effectiveness in the coming months.